Biodiversity of Banana Trees (Musa sp.) in Purwodadi Botanical Gardens - Zahro, Shofiyyatuz; Faridotul Khoiriyah, Lina; Dyana, Hanif; Haikal, Ahmad; Febrianai, Asri (Berkala Ilmiah Biologi, 2024)
Banana is a fruit that is often found in everyday life. This fruit is a daily consumption to meet daily nutritional needs. Indonesia has approximately 200 types of bananas scattered throughout the island. Diversity of banana trees (Musa sp.) in an effort to conserve Indonesian plants that live in lowland forests by carrying out plant exploration and collection activities. This research was conducted at the Purwodadi Botanical Gardens (KRP) with the aim of knowing the collection of banana trees (Musa sp.) in KRP. The method used is the roaming method with observation data collection. The results showed that there were 44 species of banana trees (Musa sp.) found alive, including the wild species with seeds Musa acuminate Colla and Musa balbisiana Colla. The species found consisted of 6 kinds of cultivar genome groups that had different characteristics. Banana tree cultivation was developed because it has many benefits and nutritional content for health.